Factor H-related protein 1 in systemic lupus erythematosus - Kleer, Jessica S.; Klehr, Juliane; Dubler, Denise; Infanti, Laura; Chizzolini, Carlo; Huynh-Do, Uyen; Ribi, Camillo; Trendelenburg, Marten (Frontiers in Immunology, 2024)
Background Factor H (FH) is a major soluble inhibitor of the complement system and part of a family comprising five related proteins (FHRs 1–5). Deficiency of FHR1 was described to be linked to an elevated risk of systemic lupus erythematosus (SLE). As FHR1 can partially antagonize the functionality of FH, an altered FHR1/FH ratio could not only enhance SLE vulnerability but also affect the disease expression. This study focuses on the analysis of FH and FHR1 at a protein level, and the occurrence of anti-FH autoantibodies (anti-FH) in a large cohort of SLE patients to explore their association with disease activity and/or expression. Methods We assessed FH and FHR1 levels in plasma from 378 SLE patients compared to 84 healthy controls (normal human plasma, NHP), and sera from another cohort of 84 healthy individuals (normal human serum, NHS), using RayBio® CFH and CFHR1 ELISA kits. Patients were recruited by the Swiss SLE Cohort Study (SSCS). Unmeasurable FHR1 levels were all confirmed by Western blot, and in a subgroup of patients by PCR. Anti-FH were measured in SLE patients with non-detectable FHR1 levels and matched control patients using Abnova’s CFH IgG ELISA kit. Results Overall, FH and FHR1 levels were significantly higher in healthy controls, but there was no significant difference in FHR1/FH ratios between SLE patients and NHPs. However, SLE patients showed a significantly higher prevalence of undetectable FHR1 compared to all healthy controls (35/378 SLE patients versus 6/168 healthy controls; p= 0.0214, OR=2.751, 95% CI = 1.115 – 8.164), with a consistent trend across all ethnic subgroups. Levels of FH and FHR1, FHR1/FH ratios and absence of FHR1 were not consistently associated with disease activity and/or specific disease manifestations, but absence of FHR1 (primarily equivalent to CFHR1 deficiency) was linked to the presence of anti-FH in SLE patients (p=0.039). Conclusions Deficiency of FHR1 is associated with a markedly elevated risk of developing SLE. A small proportion of FHR1-deficient SLE patients was found to have autoantibodies against FH but did not show clinical signs of microangiopathy.